2017
DOI: 10.1080/02713683.2017.1396617
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor in Patients with Primary Open-Angle Glaucoma and Age-related Cataract

Abstract: BDNF contents are decreased in AH, LF, and BS of patients with POAG demonstrating a significant decrease in the early POAG and relative increase in the next stages of the disease. A strong correlation exists between BDNF contents in AH and LF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 50 publications
3
54
1
1
Order By: Relevance
“…Clinically, investigators in Iran reported that serum BDNF concentrations decreased more in primary open angle glaucoma (POAG) and NTG patients than in normal patients 14,15 . Recently, similar results were reported from Italy 16 , Turkey 17 , and Russia 18 . BDNF is transported retrogradely from the superior colliculus to the RGCs, and this transport is substantially inhibited by acute IOP elevation 1 .…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Clinically, investigators in Iran reported that serum BDNF concentrations decreased more in primary open angle glaucoma (POAG) and NTG patients than in normal patients 14,15 . Recently, similar results were reported from Italy 16 , Turkey 17 , and Russia 18 . BDNF is transported retrogradely from the superior colliculus to the RGCs, and this transport is substantially inhibited by acute IOP elevation 1 .…”
Section: Introductionsupporting
confidence: 81%
“…Various studies have pointed out the importance of BDNF in glaucoma [14][15][16][17][18][19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Shpak et al, 55 investigating BDNF levels in primary open angle glaucoma, age-related cataract, and healthy subjects, they did not find any significant difference in the BDNF levels of lacrimal fluid (LF) and the serum of healthy controls and patients with cataract, confirming that age-related cataract has little or no effect on the BDNF level in the LF and serum. They also determined a strong correlation of BDNF levels in AH and LF, suggesting that age-related cataract does not influence BDNF level in AH as well, and they suggested that data of patients with age-related cataract could be used as normative data.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have reported on different biologic substances in the LF, implying that the changes in the concentration in LF could be indicative of changes in the substances’ intraocular levels. For example, a decrease in the BDNF level in LF in glaucoma was regarded as a possible indicator of the BDNF decline in the eye [ 36 ], although such an assumption has not been justified. Therefore, the second objective of this study was to determine the interrelations between CNTF concentrations in the eye (in AH) and in LF.…”
Section: Discussionmentioning
confidence: 99%